2002
DOI: 10.1016/s0886-3350(02)01211-7
|View full text |Cite
|
Sign up to set email alerts
|

Sulcus implantation of a 3-piece, 6.0 mm optic, hydrophobic foldable acrylic intraocular lens in phacoemulsification complicated by posterior capsule rupture

Abstract: To evaluate the safety of implanting a 3-piece, 6.0 mm optic, foldable acrylic intraocular lens (IOL) in cases of posterior capsule rupture during phacoemulsification. Department of Ophthalmology, Ahepa Hospital, Aristotle University Medical School, and Interbalkan Medical Center, Thessaloniki, Greece. This prospective noncomparative case series included 28 eyes (28 patients) having phacoemulsification complicated by extensive posterior capsule rupture with or without vitreous loss. In all eyes, a 3-piece, 6.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…Viscoelastic material remaining in the anterior chamber, the presence of preoperative glaucoma, trabecular blockage by dispersed lens particles and iris pigments, and mechanical damage in the trabecular meshwork can raise postoperative IOP. Yap and Heng 21 reported temporary increased IOP in 6 eyes (13.6%), Brazitikos et al 6 in 39%, and Basti and coauthors 17 in 15%. We observed raised IOP in 17 eyes (19.10%), and this persisted in the later period in 12 eyes (13.48%).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Viscoelastic material remaining in the anterior chamber, the presence of preoperative glaucoma, trabecular blockage by dispersed lens particles and iris pigments, and mechanical damage in the trabecular meshwork can raise postoperative IOP. Yap and Heng 21 reported temporary increased IOP in 6 eyes (13.6%), Brazitikos et al 6 in 39%, and Basti and coauthors 17 in 15%. We observed raised IOP in 17 eyes (19.10%), and this persisted in the later period in 12 eyes (13.48%).…”
Section: Resultsmentioning
confidence: 94%
“…Brazitikos et al 6 and Amino and Yamakawa 8 reported that postoperative inflammation was more severe in eyes with posterior capsule tear. Amino and Yamakawa 8 reported that anterior chamber reaction was greater in eyes with sulcus-to-sulcus fixation because of contact between the IOL optic and the iris and that this persisted, albeit at a low level, for a long time after surgery; the presence of this contact was revealed by ultrasound biomicroscopy (UBM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations